A functional genomics screen identifying blood cell development genes in Drosophila by undergraduates participating in a course-based research experience. Issue 1 (30th January 2021) - Evans, Cory J; Olson, John M; Mondal, Bama Charan; Kandimalla, Pratyush; Abbasi, Ariano; Abdusamad, Mai M; Acosta, Osvaldo; Ainsworth, Julia A; Akram, Haris M; Albert, Ralph B; Alegria-Leal, Elitzander; Alexander, Kai Y; et al.
Abstract: Undergraduate students participating in the UCLA Undergraduate Research Consortium for Functional Genomics (URCFG) have conducted a two-phased screen using RNA interference (RNAi) in combination with fluorescent reporter proteins to identify genes important for hematopoiesis in Drosophila . This screen disrupted the function of approximately 3500 genes and identified 137 candidate genes for which loss of function leads to observable changes in the hematopoietic development. Targeting RNAi to maturing, progenitor, and regulatory cell types identified key subsets that either limit or promote blood cell maturation. Bioinformatic analysis reveals gene enrichment in several previously uncharacterized areas, including RNA processing and export and vesicular trafficking. Lastly, the participation of students in this course-based undergraduate research experience (CURE) correlated with increased learning gains across several areas, as well as increased STEM retention, indicating that authentic, student-driven research in the form of a CURE represents an impactful and enriching pedagogical approach.